The Role of Magnetic Resonance Imaging in the Intra-Operative Evaluation of Fistula in Ano - Iqra, Iqra Aslam; Nadeem Ibrahim; Naima Rauf; Amer Hayat Haider; Sadia Tahir; Jahanzeb Javed (Medical Journal of South Punjab, 2025)
Abstract:  Objective: assessing the role of magnetic resonance (MRI) imaging in intraoperative evaluation of fistula in ano.Study Type: Cross Sectional Analytical StudyStudy Place and Duration: Department of Radiology, Combined Military Hospital Gujranwala, from September 1, 2023 to August 30, 2024.Material and methods: Sixty patients were referred to the hospital's Radiology Department. Subsequently, these patients were referred for MRI scans in the Radiology Department. The MRI scanner used was equipped with a 16 channel body coil and a surface-coil. The data of all 60 patients who underwent surgical intervention were included in the study. The interval between MRI and surgery was from one week to two months. The gold standard was considered to be surgical findings, which were recorded independently by the surgeon. The researcher personally collected the data for the study and analyzed using SPSS version24. Continuous variables (age) were examined using descriptive statistics, namely; standard and mean deviation while categorical variables (gender) were using frequency and percentage.Results: Diagnostic performance indicated sensitivity (94.9%) and specificity (100.0%). The PPV was 100.0%, and the NPV was 25.0%, with an overall diagnostic accuracy of 95.0%.Conclusion: MRI offers precise anatomical and pathological information essential for directing pre-surgical decisions and planning in the management of perianal fistulas.Keywords: Magnetic Resonance Imaging (MRI), Intra-operative, Evaluation, Fistula in Ano, Accuracy, Sensitivity, Specificity.